Synthesis and Characterization of Novel Fluoro‐glycosylated Porphyrins that can be Utilized as Theranostic Agents. Issue 7 (1st June 2018) - Arja, Katriann; Elgland, Mathias; Appelqvist, Hanna; Konradsson, Peter; Lindgren, Mikael; Nilsson, K. Peter R.
Abstract: Invited for this month's cover picture is the group of Professor Peter Nilsson at the Department of Physics, Chemistry and Biology at Linköping University (Sweden). The cover picture shows a fluoro‐glycoporphyrin that selectively targets cancer cells. The selectivity towards cancer cells are afforded due to proper functionalization of the porphyrin scaffold with specific carbohydrates, and the cancer cells can be visualized because of the intrinsic fluorescence from the porphyrin. The molecule also exhibits properties for photodynamic therapy and the incorporation of fluorine, in the form of 2‐fluoro‐2‐deoxy glucose (FDG), offers the possibility to apply these compounds as 18F positron emission tomography (PET) tracers. Thus, fluoro‐glycoporphyrins display multimodal properties and can be employed as theranostic agents targeting cancer cells. Read the full text of their Full Paper at10.1002/open.201800020 . Abstract : " Fluoro‐glycosylated porphyrins are theranostic agents that exhibit properties for multimodal imaging and photodynamic therapy, as well as specificity towards distinct molecular targets such as cancer cells. Desired carbohydrate functionalization can be afforded by sequential click‐chemistry reactions …" Find out more about the story behind the front cover research at10.1002/open.201800020 .